A simple and low temperature process for super-hydrophilic rutile TiO2 thin films growth - Mane, R. S.; Joo, Oh-Shim; Min, Sun-Ki; Lokhande, C. D.; Han, Sung-Hwan (ELSEVIER, 2006)
We investigate an environmentally friendly aqueous solution system for rutile TiO2 violet color nanocrystalline thin films growth on ITO substrate at room temperature. Film shows considerable absorption in visible region with excitonic maxima at 434 nm. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED), UV-vis, water surface contact angle and energy dispersive X-ray analysis (EDX) techniques in addition to actual photo-image that shows purely rutile phase of TiO2 with violet color. super-hydrophilic and densely packed nanometer-sized spherical grains of approximate diameter 3.15 +/- 0.4 nm, characterize the films. Band gap energy of 4.61 eV for direct transition was obtained for the rutile TiO2 films. Film surface shows super-hydrophilic behavior, as exhibited water contact angle was 7 degrees. Strong visible absorption (not due to chlorine) leaves future challenge to use these films in extremely thin absorber (ETA) solar cells. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ANATASE; DEPOSITION; NANOCRYSTALS; HYDROLYSIS; PARTICLES; SIZE; ION